Revisiting the Chemical Stability of Germanium Selenide (GeSe) and the Origin of its Photocatalytic Efficiency. (17th September 2021) - Boukhvalov, Danil W.; Nappini, Silvia; Vorokhta, Mykhailo; Menteş, Tevfik Onur; Piliai, Lesia; Panahi, Mohammad; Genuzio, Francesca; De Santis, Jessica; Kuo, Chia‐Nung; Lue, Chin Shan; Paolucci, Valentina; Locatelli, Andrea; et al.
Abstract: Recently, germanium selenide (GeSe) has emerged as a promising van der Waals semiconductor for photovoltaics, solar light harvesting, and water photoelectrolysis cells. Contrary to previous reports claiming perfect ambient stability based on experiments with techniques without surface sensitivity, here, by means of surface‐science investigations and density functional theory, it is demonstrated that actually both: i) the surface of bulk crystals; and ii) atomically thin flakes of GeSe are prone to oxidation, with the formation of self‐assembled germanium‐oxide skin with sub‐nanometric thickness. Surface oxidation leads to the decrease of the bandgap of stoichiometric GeSe and GeSe1− x, while bandgap energy increases upon surface oxidation of Ge1− x Se. Remarkably, the formation of a surface oxide skin on GeSe crystals plays a key role in the physicochemical mechanisms ruling photoelectrocatalysis: the underlying van der Waals semiconductor provides electron–hole pairs, while the germanium‐oxide skin formed upon oxidation affords the active sites for catalytic reactions. The self‐assembled germanium‐oxide/germanium‐selenide heterostructure with different bandgaps enables the activation of photocatalytic processes by absorption of light of different wavelengths, with inherently superior activity. Finally, it is discovered that, depending on the specific solvent‐GeSe interaction, the liquid phase exfoliation of bulk crystals can induce the formation of Se nanowires. Abstract : The formation of a surface oxide skin on GeSe crystals plays a key role in the physicochemical mechanisms ruling photoelectrocatalysis: the underlying van der Waals semiconductor provides electron–hole pairs, while the germanium‐oxide skin formed upon oxidation affords the active sites for catalytic reactions.